Key Sectors Driving Saudi Vision 2030 Diversification - Brika, Said khalfa; Adli, Brahim; Mili, Khaled; Bengana, Ismail; Khababa, Nourredine (Journal of Posthumanism, 2025)
Saudi Arabia’s Vision 2030 is quite an important strategy to decrease the dependency on oil and build a more robust and more sustainable economy. This paper uses input-output analysis to map out the strength of some sectoral interactions and multiplier effects in order to figure out the economic value of key sectors. While employing backwards and forward linkages, the research explains the role that manufacturing, agriculture, tourism, technology, and renewable energy sectors have in growth, employment, and competitiveness. About the results, the manufacturing industry is identified as a crucial sector due to its high degree of interconnection with the rest of the economy, thereby enhancing diversification efforts. The agriculture sector, however, does exhibit strong backward linkages as it is a key supplier of many sectors, and tourism and entertainment sectors serve to strengthen forward linkages by encouraging such ancillary sectors as hotels and transport industries. The dominion of technology in society is highlighted as a driver of change that encourages economic growth and assists the Kingdom in its shift to the Industry era. In addition, renewable energy is compatible with sustainability objectives in the world as it creates significant positive impacts on the economy through investments targeting solar and wind energy. The paper emphasizes precision concerning policies aimed at promoting linkages between industries to engender balanced growth. By focusing on high-impact industries, Saudi Arabia will be able to fully meet the long-term goals embedded in Vision 2030. The evidence generated from the research brings us useful recommendations for Malaysia, in particular for policymakers and stakeholders dealing with resource allocation in striving for a sustainable, multifunctional economy.